PERILAKU HARIAN ORANGUTAN (Pongo pygmaeus) DI YIARI KETAPANG, KALIMANTAN BARAT - Purnawan, Heri; Prayogo, Hari; Anwari, M Sofwan (Universitas Tanjungpura, 2016)
Forest ecosystem destruction is the biggest threat faced by orangutans, with narrower habitat because the area that became home clear land for oil palm plantations, mining, and the trees were felled for timber. Given the decreasing orangutan population caused by various factors, however, the organization Rehabilitation International Animal Rescue Foundation Indonesia (YIARI) Ketapang increasingly concerned and active to jointly maintain and conserve orangutans to avoid extinction. The purpose of this study to know the daily behavior of orangutan (Pongo pygmaeus) in (YIARI) Ketapang. Observation is done by using the Focal Animal Sampling method. Based on the results and discussion. Daily Activities vary every orangutan, orangutans voice activity often occurs in the morning usually on waking. Activity breaks every different age classes, age classes adult orangutan more social activities and rest. Activities make more of an orangutan nest three year old in comparison with adult orangutans. Activities eating more of an orangutan who was three years old. Activities switching always occurs throughout the day together Joni, Pinoh and Vijay but differ with fanfare and Lisa smaller than the other individuals.